Drift correction of the analyzed area during the study of the lateral elemental composition distribution in single semiconductor nanostructures by scanning Auger microscopy - Ponomaryov, S.S.; Yukhymchuk, V.O.; Valakh, M.Ya. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
The main difficulty in obtaining the lateral elemental composition distribution
maps of the semiconductor nanostructures by Scanning Auger Microscopy is the thermal
drift of the analyzed area, arising from its local heating with the electron probe and
subsequent shift. Therefore, the main goal of the study was the development of the
effective thermal drift correction procedure. The measurements were carried out on
GeSi/Si nanoislands obtained with molecular beam epitaxy by means of Ge deposition on
Si(100) substrate. Use of the thermal drift correction procedure made it possible to get
the lateral elemental composition distribution maps of Si and Ge for various types of
GeSi/Si nanoislands. The presence of the germanium core and silicon shell in both the
dome GeSi/Si nanoislands and pyramid ones was established. In the authors’ opinion,
this type of elemental distribution is a result of the completeness of the interdiffusion
processes course in the island/wetting layer/substrate system, which play the key role in
the nucleation, evolution and growth of GeSi/Si nanoislands. The proposed procedure of
the thermal drift correction of the analyzed area allows direct determination of the lateral
composition distribution of the GeSi/Si nanoislands with the size of the structural
elements down to 10 nm.